Sanksi Pidana terhadap Pelaku Pencemaran Nama Baik Melalui Media Sosial - I Putu Pande Juli Artana; I Nyoman Gede Sugiartha; I Made Minggu Widyantara (Jurnal Interpretasi Hukum, 2022)
People in Indonesia do not understand what the law really is, they only know that if there is a mistake, there will be punishment. The lack of insight of the Indonesian people in understanding the law makes the government always socialize how important it is that people learn the law and apply sanctions for someone who violates the law. This research aims to analyze the form of legal settlement arrangements against perpetrators of defamation through social media, as well as to discuss criminal sanctions against perpetrators of defamation through social media. The research method used is normative by using a statutory approach and a conceptual approach. The sources of legal materials in this research are primary sources of material originating from arrangements related to cases and secondary sources of material derived from legal books and journals. The data collection technique used the technique of recording and documenting data related to the case. The sophistication of the development of computer technology, especially in the telecommunications system, gave birth to a new term called the internet. The internet is one of the media electronic in terms of information and communication that is able to connect people around the world, so that the world feels increasingly narrow and without boundaries because of the ease in establishing communication. Globalization that gave birth to internet-based information and communication technology has shaped the pattern of human life with a new culture. With the internet, people are no longer worried about boundaries of territory, space, and time that hinder the process of information and communication because they have found a way that is more effective and efficient.